2019
DOI: 10.3390/catal9070586
|View full text |Cite
|
Sign up to set email alerts
|

European Regulatory Framework and Particulate Matter Emissions of Gasoline Light-Duty Vehicles: A Review

Abstract: The particulate matter (PM) emissions of gasoline vehicles were much lower than those of diesel vehicles until the introduction of diesel particulate filters (DPFs) in the early 2000s. At the same time, gasoline direct injection (GDI) engines started to become popular in the market due to their improved efficiency over port fuel injection (PFI) ones. However, the PM mass and number emissions of GDI vehicles were higher than their PFI counterparts and diesel ones equipped with DPFs. Stringent PM mass levels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 252 publications
5
60
0
2
Order By: Relevance
“…Consequently, the PM mass and number emissions of GDI vehicles may also exceed those of diesel vehicles equipped with modern DOCs and DPFs. The rapidly increasing number of GDI vehicles led the EU administrators to make stricter limits for the PM mass levels and a new standard of PN limits for GDI vehicles in the EU, prompting the development of gasoline particulate filters in newer GDI models 71 .…”
Section: Ufps From Gasoline Direct Injection Engine Exhaustmentioning
confidence: 99%
“…Consequently, the PM mass and number emissions of GDI vehicles may also exceed those of diesel vehicles equipped with modern DOCs and DPFs. The rapidly increasing number of GDI vehicles led the EU administrators to make stricter limits for the PM mass levels and a new standard of PN limits for GDI vehicles in the EU, prompting the development of gasoline particulate filters in newer GDI models 71 .…”
Section: Ufps From Gasoline Direct Injection Engine Exhaustmentioning
confidence: 99%
“…However, the reduced degree of mixing in the combustion chamber entails the production of a greater range and quantity of noxious combustion by-products in the fuel-rich regions of the flame, e.g., unburned hydrocarbons and carbonaceous particulate matter (soot) [3][4][5][6]. Since the actual regulations strictly limit not only the mass but also the number of solid particles that can be emitted, GDI vehicles have been equipped with a Gasoline Particulate Filter (GPF) in order to keep the emissions within the limits [1,5,7]. The structure and operating principle of a GPF are similar to that of a Diesel Particulate Filter (DPF), but the regeneration phase is more critical due to the lack of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of sub-23 nm particles were sometimes found for gasoline port fuel injection (PFI) vehicles, depending on the additives used [19]. A recent review found that PFI vehicles can exceed the PN limit, but also that the concentration of particles not counted can be as high as of those >23 nm [20]. Mopeds and motorcycles have also high sub-23 nm percentages [21,22].…”
Section: Introductionmentioning
confidence: 99%